Six Thinking Hats model of learning-Creative teaching method in physiotherapy-A pilot study - Nidhi P. Vedawala; Sakshi J. Thakrar; Jayesh V. Thakrar; Pratik G. Patel; Yash G. Patel (Wolters Kluwer Medknow Publications, 2024)
BACKGROUND: The fast growth of science and technology in the 21st century has made it necessary for advances in many sectors, including social, economic, educational, and health. Physiotherapists must have highly developed critical thinking abilities, such as creative, critical, problem-solving, and analytical thinking, to deal with these changes. Creativity is the capacity to view, shape, and organize the world in a unique way, whereas critical thinking is the ability to think outside the box, notice parts that others cannot see, be open to new ideas, and never be afraid to attempt new things. All of the continually developing and changing knowledge cannot be included in educational programs for physiotherapy students. The Six Thinking Hats were designed by Edward de Bono. The "Six Thinking Hats" concept is a teaching strategy for encouraging creative thinking by organizing and presenting ideas within a predetermined framework. The goal of the study was to apply the Six Thinking Hats model to physiotherapy themes in order to create a creative teaching technique and get feedback by fostering the critical thinking abilities of physiotherapy students. MATERIALS AND METHODS: During the 2021-2022 academic year, there were 42 students registered for III and IV BPT students enrolled for physiotherapy course; however, the research sample comprised 41 students. The course included 6 h of theory and 18 h of clinical sessions. Students were taught by two instructors via a PowerPoint presentation on SCI, obesity, and for further practice, they were given two case studies taught by Six Thinking Hats model. After the class, each group received a set of hats in one of six colors to use the Six Thinking Hats method effectively, and then students were asked to provide opinions on the Six Thinking Hats model of learning. Data analysis and response reporting were conducted, using literature and student comments. RESULTS: The Six Thinking Hats model was discovered to be more efficient in comprehending topics and provides all-encompassing care. The ability to understand patients' views, see both the positive and negative aspects in conditions, develop their ability to think critically, and create with unique concepts all improved for the students. About 90.2% of students stated that they learned to think from different aspects, 85.4% of the students stated that it ensured they considered the patient holistically, 87.8% of the students stated that the method allowed for sharing different ideas and thoughts, 75.6% that it helped them to produce creative ideas. Overall, 95% of students agreed that the Six Thinking Hats approach was better than conventional lectures and case studies, with 5% disagreeing. CONCLUSION: This study concluded that the Six Thinking Hats model of learning is a creative teaching method that is useful for the development of physiotherapy students' critical thinking. Skills and having this type of study in the physiotherapy literature add to the improvement and enrichment of physiotherapy education.